2018
DOI: 10.1155/2018/2367615
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Achilles Tendon Rupture Have a Degenerated Contralateral Achilles Tendon: An Elastography Study

Abstract: Purpose To evaluate differences of Achilles tendon (AT) hardness and morphology between asymptomatic tendons in patients with acute AT ruptures on the contralateral side and asymptomatic tendons in healthy people by using computer-assisted quantification on axial-strain sonoelastography (ASE). Methods The study consisted of 33 asymptomatic tendons in 33 patients (study group) and 34 tendons in 19 healthy volunteers (control group). All the tendons were examined by both ASE and conventional ultrasound. Computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Recent report revealed softer contralateral tendon in patients with acute AT rupture, which is similar as our finding [25]. However, this study was conducted by strain elastography that calculates elastographic value based on compression force of examiner.…”
Section: Discussionsupporting
confidence: 88%
“…Recent report revealed softer contralateral tendon in patients with acute AT rupture, which is similar as our finding [25]. However, this study was conducted by strain elastography that calculates elastographic value based on compression force of examiner.…”
Section: Discussionsupporting
confidence: 88%
“…The second most striking result of this study was that, even though weight-bearing capacity for most patients was almost fully recovered after three months, shear wave velocity remained ~ 40% lower in the injured (proximal) area compared to the healthy tendon, which itself remained stable over the 12-week observation period. On this last point, it is interesting to note that other studies have reported a decrease in stiffness in the non-ruptured www.nature.com/scientificreports/ side 29,30 . While recent SWE data also showed that repaired tendons gradually become stiffer postoperatively 31 , our results clearly indicated that tendon healing is still incomplete within 3-month after the rupture, even though patients at this stage typically reached a range of motion from the ankle to the foot that is at least sufficient enough for short distance normal walking.…”
Section: Discussionmentioning
confidence: 88%
“…To evaluate the contralateral Achilles tendon in patients with acute Achilles tendon rupture, Qianru et al 25 performed computer-assisted quantification on axial-strain sonoelastography and compared symptomatic Achilles tendons with asymptomatic Achilles tendon in healthy volunteers. They found that asymptomatic contralateral Achilles tendons were softer than those of healthy controls at the proximal third, and they suspected that it may be a detectable sign of an early degenerated lesion.…”
Section: Discussionmentioning
confidence: 99%